An Updated Review on the Phytochemistry, Pharmacology, and Clinical Trials of Salacia oblonga - Kushwaha, Priya Singh; Singh, Ashok K.; Keshari, Amit K.; Maity, Siddhartha; Saha, Sudipta (Pharmacognosy Reviews)
Salacia oblonga (S. oblonga), a perennial herb, has been used for thousands of years in ayurvedic medicine and is closely associated with prevention, treatment, and cure of various human ailments such as obesity and diabetes. A vast and wide range of chemical compounds such as polyphenols, friedelane‑type triterpenes, norfriedelane‑type triterpenes, eudesmane‑type sesquiterpenes including various glycosides had been isolated from this plant. This review is aimed to survey the literature covering the phytochemistry and pharmacology of S. oblonga and to review the scientific data including active components and their multi‑targeted mechanisms of action against various metabolic syndromes. We also included clinical trials related to this plant in this review. The overview would assist researchers to gather scientific information related to S. oblonga in future.
Keywords: Clinical trials; pharmacology; phytochemistry; Salacia oblonga